2018
DOI: 10.4103/jrms.jrms_970_17
|View full text |Cite
|
Sign up to set email alerts
|

Effects of coenzyme Q10 supplementation on the serum levels of amylase, adenosine deaminase, catalase, and total antioxidant capacity in women with type 2 diabetes mellitus: A randomized, double-blind placebo-controlled trial

Abstract: Background:Increased levels of reactive oxygen species is a key factor involved in the pathogenesis of type 2 diabetes mellitus (T2DM). Coenzyme Q10 (CoQ10) is a nonenzymatic antioxidant that restores other antioxidants.Materials and Methods:This randomized, double-blind placebo-controlled trial study has been designed to evaluate the effects of CoQ10 supplementation on serum values of amylase, adenosine deaminase, catalase (CAT), total antioxidant capacity (TAC) and the quantitative insulin sensitivity check … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…These results are consistent with some previous report investigations which exhibited that the serum levels CAT, GSH, SOD, and GSH-Px are lower in DM patients as compared to the control group (Arpaci et al, 2020, Dworzański et al, 2020, Arribas et al, 2016. However, the results of this study are in disagreement with the results of a previous study that demonstrated the CAT level in serum DM patients is significantly higher than in the healthy group (Zarei et al, 2018). Recently similar patterns of data have been obtained, about a decrease in CAT, GSH, SOD, and GSH-Px serum levels in DM patients (Feng et al, 2020, Onyibe et al, 2021, Ling et al, 2020.…”
Section: Resultssupporting
confidence: 86%
“…These results are consistent with some previous report investigations which exhibited that the serum levels CAT, GSH, SOD, and GSH-Px are lower in DM patients as compared to the control group (Arpaci et al, 2020, Dworzański et al, 2020, Arribas et al, 2016. However, the results of this study are in disagreement with the results of a previous study that demonstrated the CAT level in serum DM patients is significantly higher than in the healthy group (Zarei et al, 2018). Recently similar patterns of data have been obtained, about a decrease in CAT, GSH, SOD, and GSH-Px serum levels in DM patients (Feng et al, 2020, Onyibe et al, 2021, Ling et al, 2020.…”
Section: Resultssupporting
confidence: 86%
“…Khosrowbeygi et al found that consuming 100 mg/day of CoQ10 raised TAC, catalase activity, and QUICKI, while decreasing oxidative stress and fasting blood sugar (FBS) levels in women with T2DM [54]. Similarly, Hosseinzadeh-Attar et al reported that giving 200 mg/day of CoQ10 to T2DM patients resulted in a substantial decrease in HbA1c levels, indicating better glycemic management.…”
Section: Te Role Of Coq10 In Mitigating Oxidative Stress and Its Impa...mentioning
confidence: 99%
“…Some 15 randomised controlled clinical trials supplementing CoQ10 (typically 100–200 mg/day for 3–6 months) in type II diabetic patients are currently listed by Medline. Although Eriksson et al [23] found no significant benefit of CoQ10 supplementation on glycaemic control in type II diabetics, subsequent studies reported CoQ10 supplementation significantly improved fasting plasma glucose and HbA1c (glycated haemoglobin )levels [24,25,26,27,28].…”
Section: Diabetesmentioning
confidence: 99%